The Fluidity of Integrity: Lessons from Dutch Scandals. (2nd January 2021) - Kerkhoff, Toon; Overeem, Patrick
Abstract : This article discusses how integrity scandals often amount to setting new norms besides confirming existing ones. Historical research into Dutch integrity scandals shows how integrity acquires meaning in a complex, heterogeneous, and changing environment. Far from being fixed, integrity is a moving target; rather than being simply morally wrong or illegal, actions often fit in a grey area of contestation. Based on integrity's fluidity, four possible lines of action are offered to clarify and resolve lingering difficulties in current (Dutch) integrity management. First, since integrity norms are socially constructed and changeable, they can be actively influenced. Second, there is a need for more prudence to avoid integritism. Third, it seems pertinent to revisit the common reflex to focus on compliance by adding rules. Fourth, there is a need to acknowledge the importance of proactive, democratic debate when establishing integrity norms between important stakeholders.